2020
DOI: 10.1101/lm.051201.119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a TrkB agonist on spatial and motor learning in the Ube3a mouse model of Angelman syndrome

Abstract: Angelman syndrome is a rare neurodevelopmental disorder caused by a mutation in the maternal allele of the gene Ube3a. The primary symptoms of Angelman syndrome are severe cognitive deficits, impaired motor functions, and speech disabilities. Analogous phenotypes have been detected in young adult Ube3a mice. Here, we investigate cognitive phenotypes of Ube3a mice as compared to wild-type littermate controls at an older adult age. Water maze spatial learning, swim speed, and rotarod motor coordination and balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…BDNF has a well-established role as a regulator of synaptic plasticity, dendritic outgrowth, dendritic spine formation and maintenance. Reduced levels of BDNF signaling have been reliably observed in the AS mouse model [68,69]. Previously, our team reported BDNF-induced signaling requires TrkB association with PSD-95, and disruption of this association, in the AS mouse model, which likely underlies AS deficits in learning and memory [30,31] and elevated seizure and spike train phenotypes.…”
Section: Discussionmentioning
confidence: 96%
“…BDNF has a well-established role as a regulator of synaptic plasticity, dendritic outgrowth, dendritic spine formation and maintenance. Reduced levels of BDNF signaling have been reliably observed in the AS mouse model [68,69]. Previously, our team reported BDNF-induced signaling requires TrkB association with PSD-95, and disruption of this association, in the AS mouse model, which likely underlies AS deficits in learning and memory [30,31] and elevated seizure and spike train phenotypes.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, among studies that have tested novel therapeutic approaches in AS model mice, some of the highly reproducible behavioral phenotypes are more frequently rescued than others. Across 16 recent studies that were able to rescue at least one of the behaviors tested here, motor coordination deficits on the rotarod were most commonly corrected, with the phenotype completely or partially rescued in over half of the studies (nine of 16: Adhikari et al., 2021 ; Cruz et al., 2021 ; Guzzetti et al., 2018 ; Judson et al., 2021 ; Kumar et al., 2019 ; Schmid et al., 2021 ; Silva‐Santos et al., 2015 ; Van Woerden et al., 2007 ; Wolter et al., 2020 ) and no rescue in the rest of the studies (Berg et al., 2020 ; Gu et al., 2019 ; Hethorn et al., 2015 ; Milazzo et al., 2021 ; Schultz & Crawley, 2020 ; Sonzogni et al., 2018 ; Wang et al., 2019 ). Partial or complete rescue occurred least frequently in open field thigmotaxis (one of four studies in which it was examined: Guzzetti et al., 2018 ) and marble burying (four of 10 studies in which it was examined: Cruz et al., 2021 ; Judson et al., 2021 ; Schmid et al., 2021 ; Silva‐Santos et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on comparing transgenic mouse strains used to study Angelman syndrome (AS), which is a genetic disorder affecting the nervous system, and is characterized by developmental delay, intellectual disability, profound speech impairment, and problems with movement and balance (39,52). The rotarod is most often used to study balance and coordination in mouse models for AS, and has identified impaired performance across several transgenic lines (42,43,53) and been used to assess therapeutic interventions (54)(55)(56)(57)(58). A particular strength of the beam walk in comparison to the rotarod is that it enables an assessment of how the animal performs the test, not only if the animal performs it (9).…”
Section: Discussionmentioning
confidence: 99%